Comparative analysis of rhizosphere soil between three plantation types in Karst Rocky Desertification area by widely targeted metabolomics - Guo,Tongtong; Zhu,Ninghua; Pan,Ziqian; Dang,Peng (PeerJ, 2025)
Understanding the differences in rhizosphere soil microbial metabolites between severely and mildly rocky desertified areas is crucial for developing ecological restoration strategies and land management measures in rocky desertification regions. This study systematically analyzed the differences in rhizosphere soil microbial metabolites of Toona sinensis, Vernicia fordii, and Cornus wilsoniana in severely and mildly rocky desertified areas of Western Hunan using untargeted metabolomics. The results showed that the types and quantities of primary and secondary metabolites in the rhizosphere soil of severely rocky desertified areas were significantly lower than those in mildly rocky desertified areas. Additionally, under severe rocky desertification conditions, 15 common compounds (e.g., 17a-estradiol, adenine, all-trans-retinoic acid) were significantly increased in the rhizosphere soil microbial metabolites of the three tree species. These compounds may provide defense mechanisms for plants to adapt to harsh environments. KEGG metabolic pathway analysis revealed that under severe rocky desertification conditions, Toona sinensis, Vernicia fordii, and Cornus wilsoniana shared six enriched pathways, which play an important role in the biosynthesis of compounds such as phenylpropanoids and unsaturated fatty acids. By revealing the differences in rhizosphere soil microbial metabolites, this study not only deepens the understanding of rocky desertification ecosystems but also provides valuable scientific evidence for ecological restoration and sustainable land management.
Keywords: Rocky desertification; Plantations; Rhizosphere soil microorganisms; Metabolomics; KEGG